Acute Kidney Injury by Arsine Poisoning: The Ultrastructural Pathology of the Kidney. (March 2013) - Lee, Jun Young; Eom, Minseob; Yang, Jae Won; Han, Byoung Geun; Choi, Seung Ok; Kim, Jae Seok
<x xml:space="preserve">Abstract</x> Arsenic is a terribly poisonous material. There have been many reports of arsine poisoning in workers, and a few have discussed acute kidney injury by arsine. But literatures which investigated the pathologic findings are uncommon, and especially, the ones describing ultrastructural findings are rare. Here, we report an incident of acute arsine poisoning complicated by acute kidney injury and suggest the characteristics of the renal pathology in arsine-induced renal injury, especially the ultrastructural findings.